Complexity of Caribbean migration, In: Caribbean affairs, 7, (4), September/October, p.96-119. - CONWAY, Dennis (2011)
Examines the regional system of international mobility, including the importance of intra-regional mobility patterns and temporary stay-over. Concludes that international circulation, temporary stay-over and repetitive mobility are dominant in the region.
Keywords: MIGRATION; CARIBBEAN